PENGARUH PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, DAN PERCEIVED RISK TERHADAP PURCHASE DECISIONS USING SHOPEE PAYLATER PADA GENERASI Z DI DKI JAKARTA - Aulia Febrianti; Viyonila Pratiwi, Tegar Hanafi, Akhmad Najmi Salim (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to examine the effect of perceived usefulness, perceived ease of use, and perceived risk on purchase decisions using Shopee PayLater on generation Z in DKI. Jakarta, as well as the role of perceived risk as mediation. The research method used is quantitative by distributing questionnaires measured using a Likert scale. The population in this study is generation Z who uses Shopee PayLater. A sample of 100 respondents was taken using a non- probability sampling technique, namely the purposive sampling method with the criteria for respondents, namely generation Z, aged at least 18 years to 27 years old who live in DKI. Jakarta, and have used and transacted on the Shopee application with the Shopee PayLater payment method. The research data were processed using Structural Equation Modeling (SEM) techniques using Partial Least Squares (PLS) and SmartPLS4 software assistance. The results showed that perceived usefulness and perceived risk has no positive and significant effect on purchase decisions, perceived ease of use have a positive and significant effect on purchase decisions, perceived usefulness and perceived ease of use have a positive and significant effect on perceived risk. The results also reveal that perceived risk mediates the relationship between perceived usefulness and perceived ease of use on purchase decisions using Shopee PayLater.